Urban Blue-Green Spaces and tranquility: a comprehensive review of noise reduction and sensory perception integration - Shengzhi Chu; Weizhen Xu; Danyin Zhang; Jingsong Lin; Jiang Liu; Shuhu Liu; Xin-Chen Hong (Journal of Asian Architecture and Building Engineering)
Urbanization has led to a significant increase in noise pollution, severely impacting the psychological well-being of urban dwellers. This review critically evaluates the effectiveness of urban blue-green spaces in mitigating noise pollution and enhancing tranquility experiences. Initially, this study utilizes CiteSpace visualization software for bibliometric analysis to scrutinize the current research landscape and pinpoint emerging trends. We systematically searched the Web of Science (WoS) database with the following parameters: Topic = ((“noise” OR “tranquility”) AND (“soundscape” OR “green space” OR “blue space” OR “blue-green spaces”)), 2015 to 2024. Through meticulous screening, 1504 articles were selected as the final research sample. We discuss both subjective and objective methods for assessing tranquility, and we categorize and thoroughly review the various factors influencing perceptions of urban tranquility. These factors include the interplay between natural and anthropogenic soundscapes, the authenticity of visual environments, and the unique auditory characteristics of human activities. Additionally, our review highlights the pivotal role of individual behavioral propensities and cultural frameworks in crafting tranquility experiences, and proposes a shift from reactive noise prevention to proactive tranquility exposure research. The insights provided here lay a foundation for future academic exploration and offer practical guidance for planning and management of blue-green infrastructure.